Aiding Development or Aiding Politics? How Politics in Sub-Saharan Africa Impact the Efficacy of Official Development Assistance in Ethiopia - Meyer, Courtney (Consilience, 2013)
This article approaches the concept of sustainable development with a mind to the sustainability of the neoliberal economic philosophy through which official development is currently allocated. This article examines a contemporary aid-dependent state in sub-Saharan Africa, Ethiopia, to question how governance strategies impact the efficacy of official development assistance. Much contemporary development literature neglects politics, concluding that aid effectiveness is contingent on economic variables. An increasing number of econometric studies consider the impact of aid on institutions, yet few discuss the political and developmental objectives, ultimately illustrating the naïveté of the neoliberal good-governance framework and the importance of recognizing how interests, ideas, and ideologies combine to create the specificities of politics in Africa. I argue that aspects of politics in Africa such as neopatrimonialism and patronage must be recognized as ends to governance strategies and that these may sometimes take precedence; however, whether these factors impede development depends on the regime’s objectives. Although it accompanied its development efforts with human-rights abuses to secure the regime’s future, the Meles Zenawi regime nonetheless made great strides toward economic prosperity.